2015
DOI: 10.1089/humc.2015.052
|View full text |Cite
|
Sign up to set email alerts
|

Use of Adeno-Associated Virus to Enrich Cardiomyocytes Derived from Human Stem Cells

Abstract: Cardiomyocytes derived from human induced pluripotent stem cells (iPSCs) show great promise as autologous donor cells to treat heart disease. A major technical obstacle to this approach is that available induction methods often produce heterogeneous cell population with low percentage of cardiomyocytes. Here we describe a cardiac enrichment approach using nonintegrating adeno-associated virus (AAV). We first examined several AAV serotypes for their ability to selectively transduce iPSC-derived cardiomyocytes. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…We chose ChIEF because this channel does not desensitize with chronic light stimulation, and we chose an AAV1 vector because of its safety and efficient transfection of h-iPSC-CMs. 52,64,65 These three properties exhibited utility as demonstrated by the significant results of C-OP (Figures 1 and 5(b)). Similar CM percentages between D14 control and D14C-OP ECTs supported low AAV toxicity (Figure 5(e)).…”
Section: Discussionmentioning
confidence: 84%
“…We chose ChIEF because this channel does not desensitize with chronic light stimulation, and we chose an AAV1 vector because of its safety and efficient transfection of h-iPSC-CMs. 52,64,65 These three properties exhibited utility as demonstrated by the significant results of C-OP (Figures 1 and 5(b)). Similar CM percentages between D14 control and D14C-OP ECTs supported low AAV toxicity (Figure 5(e)).…”
Section: Discussionmentioning
confidence: 84%
“…To test proof of concept for gene replacement therapy in human cells, we generated an AAV, containing the N-terminal, FLAG-tagged, full-length human PKP2 sequence driven by the CMV promoter (AAV2 -PKP2 ; Figure 6 A). We selected the AAV2 serotype because AAV2 has been shown to efficiently transduce iPSC-CMs ( Guan et al., 2015 ), and the use of AAV2 led to high transduction efficiency in iPSC-CMs under our experimental conditions ( Kohama et al., 2020 ; Shiba et al., 2021 ) ( Figure S6 A). FLAG-tagged plakophilin-2 protein localized properly at the cellular periphery in iPSC-CMs ( Figure 6 B), and AAV2-mediated delivery of plakophilin-2 restored the localization of desmoglein-2, desmocollin-2, and N-cadherin in the cell-cell junctions of NHEJ-iPSC-CMs ( Figures S6 B and S6C).…”
Section: Resultsmentioning
confidence: 99%
“…AAV-mediated gene delivery of PKP2 recovered contractility and desmosome assembly in plakophilin-2-deficient iPSC-CMs To test proof of concept for gene replacement therapy in human cells, we generated an AAV, containing the N-terminal, FLAG-tagged, full-length human PKP2 sequence driven by the CMV promoter (AAV2-PKP2; Figure 6A). We selected the AAV2 serotype because AAV2 has been shown to efficiently transduce iPSC-CMs (Guan et al, 2015), and the use of AAV2 led to high transduction efficiency in iPSC-CMs under our experimental conditions (Kohama et al, (E) The images shown in (D) were quantitatively analyzed using high-content imaging. Top: raw immunostained images and captured intensity images detected using high-content imaging.…”
Section: Allele-specific Fluorescent Labeling Of Dsg2 Captures Desmosome Dynamics In Isogenic Ipsc-cmsmentioning
confidence: 99%
“…gRNA was designed in an antisense direction targeting a PAM sequence located 19 bp downstream of the MYL2 stop codon to avoid Cas9-mediated re-cleavage of exon 7. We generated AAV2 encoding a gRNA sequence and repair template, because AAV2 was previously shown to efficiently transduce hiPSC-CMs 26 , and was found to transduce hiPSC-CMs with high efficiency in our experimental conditions (Supplementary Fig. 5 B).…”
Section: Resultsmentioning
confidence: 99%